Similarity Analysis of Protein Sequences Based on the EMD Method (Journal of Fiber Bioengineering and Informatics, 2014)
An Empirical Mode Decomposition (EMD) method to analyze the similarities of protein sequences isproposed. The EMD method was used to divide a signal sequence converted from a protein sequenceinto a group of well-behaved Intrinsic Mode Functions (IMFs) and a residue which is monotonic or atrend. This is so that the similarities can be compared among protein sequences by the correspondingresidues conveniently and intuitively. This work verifies the method's suitability by using the cytochromec protein sequences of seven different species.
Keywords: MQ-RBF Quasi-interpolant; EMD; IMFs; Similarity Analysis; DNA Sequences